Bank Interest Legality Analysis Between the Perspectives of Darul Ifta’ Almishriyyah and Fatwa Authorities in the Islamic World - Fanani, Muchammad Fathoni; Nashirudin, Muh. (Jurnal Indonesia Sosial Sains, 2025)
Muslims in every activity must be based on Islamic values in order to achieve happiness in the world and the hereafter, one of which is economic activity. The essence of the prohibition of usury in Islam is to eliminate injustice and remove injustice in every economic transaction. Meanwhile, usury or interest is a form of exploitation of the upper class to the lower class by extracting maximum profit. The purpose of this research is to analyze the legality of bank interest from two authoritative perspectives in the contemporary Islamic world, namely darul ifta' almishriyyah and Fatwa Institutions in the world. These two research objects have different views on the legal status of bank interest. This study uses a qualitative-descriptive method with a normative approach and document analysis of the fatwas of these institutions. The results of the study prove that the majority of the World Fatwa Institutions tend to prohibit the practice of interest in modern banking. According to them, bank interest is not in accordance with the principle of mudhorobah and is included in the category of riba nasiah which is prohibited by Islam. The concept of usury is very far from the principle of justice and prioritizes economic exploitation of weak groups. In contrast, Egyptian fatwa institutions tend to allow lending, especially in the context of modern banking that has been regulated by the state. They have the perspective that the practice of interest that is applied by modern banking today is not included in the category of usury which is absolutely forbidden in Nash.